Ocular symptoms as the initial clinical manifestations in patients with extraocular tumors - Zheng, Jianlong (Ann Transl Med, 2021)
BACKGROUND: Due to the variety of clinical presentation, some tumors may be concealed and easily misdiagnosed, leading to delays in management. We report a series of patients who initially presented to an Ophthalmic Clinic with ocular symptoms and were subsequently diagnosed with extraocular tumors. METHODS: Patients who presented to the ophthalmic outpatient clinic at the Joint Shantou International Eye Center with ocular symptoms between April 2013 and December 2019 and were subsequently diagnosed with intracranial or systemic tumors were reviewed retrospectively. Clinical data, including ocular symptoms and signs, ophthalmic and systemic imaging examinations, and the results of tumor biopsies were collected and analyzed. RESULTS: Twenty-three patients were included in this study, of which 16 were female (69.6%) and 7 were male (30.4%). Chief complaints at the first visit included visual loss (n=20), proptosis (n=2), and diplopia (n=1). Ocular examination revealed disc pallor (n=8) and swelling (n=3), choroidal mass with or without chorioretinal detachment (n=5), and proptosis (n=2). Visual field (VF) examination was performed in 11 patients of which hemianopia (n=4) and non-specific field loss (n=7) were noted. Brain CT or MRI, together with histopathological findings from surgical biopsies confirmed the diagnosis of the intracranial tumors in 18 cases, including pituitary adenoma (n=7), meningioma (n=2), oligodendroglioma (n=1), sellar tumor (n=1), suprachiasmatic arteriovenous aneurysm (n=1), orbital glioma (n=1), multiple intracranial tumors (n=1), and sphenoid ossifying fibroma (n=1). Nasopharyngeal carcinoma (NPC) (n=3) was diagnosed with brain MRI and nasal endoscopy. Five patients were confirmed as choroidal metastasis secondary to lung cancer (n=3), hepatoma (n=1), and breast cancer (n=1). CONCLUSIONS: Patients with extraocular tumors may present initially to an ophthalmologist with ocular symptoms. It is important to identify and appropriately manage these patients to avoid unnecessary delays in future treatment.